Theory-supported corpus pedagogy for ESL pre-service teachers: using Parallel EAP Corpora for language learning - Yan, Jiahao; Ma, Qing (Journal of China Computer-Assisted Language Learning, 2025)
Corpus technology (CT) as an effective technology for language learning is slowly being adopted by in-service language teachers. However, there is limited focus on pre-service language teachers, who first need to experience CT and gain a basic corpus literacy as learners. Therefore, this research aimed to demonstrate the learning benefits of CT to pre-service teacher and explore their intentions for future use of CT. A corpus pedagogy supported by constructivism, socio-cultural theory, and noticing hypothesis, was designed to help three-classes of pre-service ESL teachers in Chinese Hong Kong to improve citation skills using Parallel EAP Corpora. A mixed-method design was adopted by collecting data via tests, surveys, classroom interactions and interviews. The results revealed that the participants learned to use reporting verbs for citations, acquired adequate corpus literacy, positively evaluated the theory-supported pedagogy, and expressed strong intentions to use CT for learning vocabulary and academic writing, conducting research to complete course assignments, and facilitating future teaching. The findings highlight the significance of designing corpus-based learning activities through theory-supported pedagogy and reveal that introducing CT to pre-service ESL teachers who have multiple identities as language learners, novice researchers, critical thinkers, and future teachers, can have important pedagogical implications.